Determinants of cardiac output in health and heart failure - Ibrahim Ainab; Natalie Van Ochten; Emmett Suckow; Kathryn Pierce; Chelsea Arent; Joseph Kay; Lindsey M. Forbes; William K. Cornwell III (Experimental Physiology)
Abstract Sustained physical exercise depends on delivery of oxygenated blood to exercising muscle. At least among healthy individuals, bulk transport of blood is tightly matched to metabolic demand, such that cardiac output increases by ∼6 L/min for every 1 L/min increase in oxygen uptake. Multiple factors contribute to the regulation of cardiac output, including central command, the exercise pressor reflex (EPR) and arterial baroreceptors. Pulmonary arterial and left ventricular pressures increase in proportion to the rise in cardiac output and exercise intensity. The right ventricle augments contractility to maintain ventricular–arterial (VA) coupling and lusitropy to facilitate venous return. Among patients with heart failure (HF), however, the ability to deliver blood to exercising muscle is compromised as a result of multiple abnormalities impacting EPR, ventricular contractility, haemodynamics and VA coupling. The purpose of this review is to provide an overview of the factors limiting exercise capacity and cardiac output among patients with HF compared to what is known about normal physiology among healthy individuals.